Efficacy of intense pulsed light therapy in the treatment of facial acne vulgaris: Comparison of two different fluences - Monika V Patidar; Ashish Ramchandra Deshmukh; Maruti Yadav Khedkar (Wolters Kluwer Medknow Publications, 2016)
Background: Acne vulgaris is the most common disease of the skin affecting adolescents and young adults causing psychological distress. The combination of antibiotic resistance, adverse effects of topical and systemic anti acne medications and desire for high tech approaches have all led to new enthusiasm for light based acne treatment. Intense pulse light (IPL) therapy has three modes of action in acne vulgaris i.e., photochemical, photo thermal and photo immunological. Aims: (1) to study efficacy of IPL therapy in facial acne vulgaris. (2) To compare two fluences - one normal and other subnormal on right and left side of face respectively. Methods: (Including settings and design and statistical analysis used). Total 45 patients in age group 16 to 28 years with inflammatory facial acne vulgaris were included in prospective study. Baseline data for each patient was recorded. All patients were given 4 sittings of IPL at 2 weeks interval and were followed for 2 months every 2 weeks. Fluence used was 35J/cm2 on right and 20J/cm2 on left side. Percentage reduction in lesion count was calculated at each sitting and follow up and graded as mild (0-25%), moderate (26-50%), good (51-75%) and excellent (76-100%). Side effects were noted. The results were analysed using Mann-Whitney Test. Results: On right side, excellent results were achieved in 10(22%), good in 22(49%) and moderate in 13(29%) patients. On left side excellent were results achieved in 7(15%), good in 19(42%) and moderate in 16(43%) patients. There was no statically significant difference noted in efficacy of two fluences used in treatment of facial acne vulgaris. Conclusions: IPL is a effective and safe option for inflammatory acne vulgaris with minimal reversible side effects. Subnormal fluence is as effective as normal fluence in Indian skin.